1989
DOI: 10.1128/iai.57.12.3808-3815.1989
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of Treponema hyodysenteriae antigens and protection in a CF-1 mouse model by immunization with a cloned endoflagellar antigen

Abstract: We cloned genes that code for Treponema hyodysenteriae antigens into Escherichia coli with the purpose of identifying protective antigens for vaccine development. Three different genomic libraries were screened with various antisera reactive with T. hyodysenteriae antigens. The cloned antigens and corresponding native T. hyodysenteriae antigens were analyzed for molecular size, serum reactivity, solubility in sarcosine, and segregation during phase partitioning with the nonionic detergent Triton X-114. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The diagnosis of swine dysentery is based on herd history, clinical signs, histopathological examination, and isolation of S. hyodysenteriae from feces (13). To date, nine serotypes and nine serogroups have been proposed, and serotypes 1, 2, 8, and 9 are most prevalent in North America (6,10,21). Although S. hyodysenteriae is the most common causative agent of swine dysentery (12,13), another species of spirochetes called Serpulina innocens, isolated from apparently healthy swine and those with postweaning scours, may also be involved in the pathogenesis of swine dysentery (16,27,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of swine dysentery is based on herd history, clinical signs, histopathological examination, and isolation of S. hyodysenteriae from feces (13). To date, nine serotypes and nine serogroups have been proposed, and serotypes 1, 2, 8, and 9 are most prevalent in North America (6,10,21). Although S. hyodysenteriae is the most common causative agent of swine dysentery (12,13), another species of spirochetes called Serpulina innocens, isolated from apparently healthy swine and those with postweaning scours, may also be involved in the pathogenesis of swine dysentery (16,27,28).…”
mentioning
confidence: 99%
“…S. hyodysenteriae is known to be antigenically heterogenous, with different serotypes showing different geographical distributions. To date, nine serotypes and nine serogroups have been proposed (6,10,13,21). The most frequently encountered strains isolated from clinical cases of swine dysentery belong to serotypes 1 and 2 in the United States, serotypes 8 and 9 in Quebec, serotypes 4 and 7 in Europe, and serogroups A, B, and E in South Australia (6,19,21).…”
mentioning
confidence: 99%
“…These proteins are probably components of the flagella (17). Furthermore, Boyden et al (2) showed that a cloned flagellar protein of S. hyodysentenae was protective in a mouse model of swine dysentery.…”
mentioning
confidence: 99%